Jewish, Christian, and Islamic Mystical Perspectives on the Love of God
VII, 188 p.
Keywords: A collection of essays in which the possibilities of a deeper dialogue, by means of the contemplative traditions of the Abrahamic Faiths is explored. The book expounds an ageless, profound means of overcoming religious hatred and violence and awakening the beauty of unity in diversity.